Renal artery embolization prior to nephrectomy for locally advanced renal cell carcinoma. Issue 7 (18th February 2014) - Zargar, Homayoun; Addison, Ben; McCall, John; Bartlett, Adam; Buckley, Brendan; Rice, Michael
Abstract Background To assess the outcomes of patients undergoing percutaneous renal artery embolization (PRAE) prior to radical nephrectomy. Methods We performed retrospective chart review of patients undergoing PRAE in Auckland Public Hospital from January 2004 to December 2011. PRAE was performed under epidural anaesthesia and within 24 h of nephrectomy. We compared our perioperative outcomes with the published literature. Results Forty‐two patients were identified in this series. Patients had predominantly more advanced stage disease with 30 (71%) being T3 or higher (TNM staging). Median operation time was 192 min (range 84–428). 45.2% of patients experienced complications from the surgery. There were no complications associated with PRAE. Conclusions PRAE prior to nephrectomy is a safe procedure. There is no convincing evidence in the literature that the benefits outweigh the risks. All published studies are non‐randomized and subject to selection bias, so the true role of PRAE has not yet been determined and routine use is probably not justified.